A 6-year survey of road traffic accidents in Southwest China: Emphasis on traumatic brain injury. (June 2020) - Duan, Aowen; Zhou, Mingxia; Qiu, Jinlong; Feng, Chengjian; Yin, Zhiyong; Li, Kui
Highlights: An up-to-date overview of patterns of injuries caused by RTAs in southwest China. Head injury still occupied the highest proportion among the injuries and deaths. It's urgently needed to develop a more reliable brain injury evaluation criterion. Emergency care to head injury at the scene is effective to reduce traffic fatality. Abstract: Background : The objective of this study is to provide an up-to-date overview of the patterns of injuries, especially traumatic brain injury (TBI) caused by RTAs and to discuss some of the public health consequences. Methods : A scientific team was established to collect road traffic accidents occurring between 2013 and 2018 in Chongqing, Southwest China. For each accident, the environment-, vehicle-, and person- variables were analyzed and determined. The overall injury distribution and TBI patterns of four types of road users (driver, passenger, motorcyclist and pedestrian) were compared. The environmental and time distribution of accidents with TBI were shown by bar and pie chart. The risks of severe brain injury whether motorcyclist wearing helmets or not were compared and the risk factors of severe TBI in pedestrian were determined by odds ratio analysis. Results : This study enrolled 2131 accidents with 2741 persons of all kind of traffic participants, 1149 of them suffered AIS1+ head injury and 1598(58%) died in 7 days. The most common cause of deaths is due to head injury with 714(85%) and 1266(79%) persons died within 2 hours. Among 423 persons suffered both skull fracture and intracranial injury, 102 (24.1%) have an intracranial injury but no skull fractures, while none of the skull fractures without intracranial injury was found. Besides, motorcyclists without a helmet were at higher risks for all the brain injury categories. The risk of pedestrian suffering severe TBI at an impact speed of more than 70 km/h is 100 times higher than that with an impact speed of less than 40 km/h. Conclusion : It is urgently needed to develop a more reliable brain injury evaluation criterion for better protection of the road users. We believe that strengthening the emergency care to head injury at the scene is the most effective way to reduce traffic fatality.